Peran Sanksi Pajak dalam Memoderasi Pengaruh antara Tingkat Penghasilan dan Implementasi Sistem Samsat Drive Thru terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Muhammad Daffa Adyazmara; Rahmasari Fahria (Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of income level and the samsat drive thru system through motor vehicle taxpayer compliance and the role of tax sanctions in moderating income level and the samsat drive thru system through motor vehicle taxpayer compliance. The populations used in this study are taxpayers who pay their motorized vehicle taxes at the Samsat Drive Thru Polda Metro Jaya, South Jakarta. Sampling in this study use accidental sampling. Sources of data in this study came from questionnaires. The data analysis method uses Structural Equation Modeling (SEM) using Smart Partial Least Square version 3.0. The results of this study indicate that the level of income has a significant effect on motor vehicle taxpayer compliance. The samsat drive thru system has no significant effect on motor vehicle taxpayer compliance. Tax sanctions are not able to moderate the effect of income levels and the samsat drive thru system on motor vehicle taxpayer compliance.